6tan(3x)=6

Simple and best practice solution for 6tan(3x)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6tan(3x)=6 equation:


Simplifying
6tan(3x) = 6

Remove parenthesis around (3x)
6ant * 3x = 6

Reorder the terms for easier multiplication:
6 * 3ant * x = 6

Multiply 6 * 3
18ant * x = 6

Multiply ant * x
18antx = 6

Solving
18antx = 6

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Divide each side by '18ntx'.
a = 0.3333333333n-1t-1x-1

Simplifying
a = 0.3333333333n-1t-1x-1

See similar equations:

| 2(4z-1)-2(5-3z)=6 | | 3(2-y)=-2 | | 6=5(k-1)+3-4K | | x=179+157 | | h=-16t^2+150+162 | | P/25=28 | | 12x+288=180 | | -12/-45 | | 5y=-2x+46 | | 4m=3m+12 | | 2y+4x=56 | | (x+3)(x^2+5x+4)=0 | | 5n^5-5n^4+6n^3-6n^2= | | 5t/7=15 | | -y^2=11 | | 7-5(8x+4)=-2 | | -26+3x=-52+9 | | 2/9s=8 | | 5x-20=12-3x | | 5b-2b-20=3b-10 | | 8+3x=5x+6 | | p(x)=x^2+1 | | mx+nz=p | | Y-9=-6(x-3) | | 5d-5=11 | | h(x)=x/2-1 | | (2x-4)(5x+9)=0 | | X/4=8.7 | | 58=27-g | | 6xy^5+3yx^4+9x^2=0 | | 20-65a-8= | | 4c-3(c-6)=2+2+2c |

Equations solver categories